A Spatial Approach to Energy Economics: Theory, Measurement and Empirics - Juan Moreno-Cruz; M. Scott Taylor (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper sets out a simple spatial model of energy exploitation to ask how the location and productivity of energy resources may affect the distribution of economic activity around the globe. We combine elements from resource and energy economics into one framework linking the spatial productivity of energy resources (both renewable and non-renewable) to the incentives for economic activity to concentrate. Our theory provides a novel scaling law; a magnification effect; and reveals a complementarity between infrastructure investment and spatially productive energy resources. Our empirical work provides estimates of key magnitudes and reviews empirical work supporting our approach.
Keywords: N50; 330; energy economics; agglomeration; economic geography